VISITORS RESPONSE ABOUT COMPONENT 4A (ATTRACTION, AMENITIES, ACCESS, ANCILLARY) IN THE MUSEUM OF THE BIRTH HOUSE OF BUNG HATTA, BUKITTINGGI CITY, WEST SUMATERA PROVINCE - Mhd. Fahrozi; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Bung Hatta Birth House Museum, Bukittinggi City, West Sumatra Province is one of the relics and from one of the Proclaimers of the Republic of Indonesia, namely Mohammad Hatta. Being one of the legacies of one of the Proclaimers of the Republic of Indonesia, it is necessary to evaluate Component 4A (Attraction, Amenities, Access, Ancillary) as a tourism product from one of the cities of Bukittinggi to be able to attract and increase visits. Feedback is one way to get a visitor's opinion on a tourist attraction visited. This study was conducted to find out how visitors respond to Component 4A (Attraction, Amenities, Access, Ancillary) at the Bung Hatta Birth House Museum, Bukittinggi City, West Sumatra Province. This study uses a quantitative method with 99 samples that have been processed by the author based on the population of the last year. The data collection technique used by the author is in the form of observations, questionnaires, documentation and uses a Likert scale as a measuring tool. Based on the results of the research, visitor responses regarding Component 4A (Attraction, Amenities, Access, Ancillary) at the Bung Hatta Birth House Museum, Bukittinggi City, West Sumatra Province, were in the very good category. Key Word: Response, Visitor, Component 4A, Tourist Attraction, Museum.